Achieving Humanist Cities: Learning From Urban Feminism and Feminist Planning - Haas, Tigran; Mehaffy, Michael (Global Journal of Cultural Studies, 2024)
As planners and urbanists continue to debate urban reforms needed to achieve humanist ideals – including just forms of sustainability – several different schools of thought are vying for influence, including cultural urbanism (celebrating the everyday, temporal, occasional, and timeless), pluralist urbanism (aiming for a co-produced city that is more democratic, participatory, and open-ended), and inclusive urbanism (focusing on the right to the city and its accommodations for all populations). Here, we examine feminist urbanism – the specific challenge of gender-equal spaces, particularly public spaces – as a model framework that suggests how the other schools of thought can be combined and translated into practical action. We focus on the nature and importance of public space and the role of gender inclusiveness in assuring public spaces that are more broadly open, participatory, pluralist, and supportive of temporal and everyday activities. We thus find that the emerging concept of feminist urbanism reveals essential issues for a wider humanist urbanism – in particular, who the city is meant to serve and whether the public realm is equitably ‘public’ to all its users. We note major remaining questions and research lacuna to be investigated, and we conclude with several policy and design recommendations.